Vincenzo Consolo: gli anni de «l'Unità» (1992-2012), ovvero la poetica della colpa-espiazione - Joseph Francese (Studi e saggi, 2015)
Vincenzo Consolo: gli anni de «l'Unità» (1992-2012), ovvero la poetica della colpa-espiazione analyses the frequent collaboration between Vincenzo Consolo (1933-2012) and the Italian newspaper «l'Unità», which started in the 1990s and would continue until the author's death. This collaboration reveals a form of political protagonism which the writer had originally shied away from. Over this period of time, in his written pieces, Consolo turns from the «contastorie consolatorio» (a consoling storyteller) into a Benjamin-style narrator, offering the new generations a progressive life model based on his own youthful experiences. This artistic development reflects in a similar transformation within his narration, and explains the reason behind the use of the first person narrator, that «impudico io» (the "impure I"), as the author himself puts it. This form of literary experimentation, which differs from the work he carried out over the previous decades, allows the writer to atone for not having done more in the Seventies and the Eighties to improve the social, environmental and political degradation whose spread he had witnessed.